Idaarati Manaahij Al-Lughah Al-‘Arabiyah bi Indonesia - Azimah, Hanifa (Al Intisyar: Jurnal Pendidikan Bahasa Arab, 2025)
This paper aims to describe the management of the Arabic curriculum, especially nahwu, at the Tahfiz Muallimin Muhammadiyah Sawah Dangka Islamic Boarding School, its positive and negative sides and its development suggestions. This study uses a descriptive qualitative method. The results of this study show the implementation of Arabic curriculum management at the Tahfiz Muallimin Muhammadiyah Sawah Dangka Islamic Boarding School using the nazhariyah furu' system. The book "Nahwu Wadhih" is used as the main teaching material for nahwu learning. Although this book has advantages such as systematic learning methods and relevant examples, there are disadvantages such as students' dependence on teachers and lack of discussion of advanced topics. The positive aspects of the Arabic curriculum in Islamic boarding schools include increased understanding of Islamic religious teachings, the development of critical thinking skills, and preparation for participation in the global job market. However, there are drawbacks such as a greater focus on theory rather than practical language skills and outdated teaching methods. For curriculum development, it is recommended that there is a clear plan, the use of interactive learning media, and periodic evaluations for continuous improvement.